An Empirical Study On The Influence Of Macroeconomic Variables On Economic Growth In East Java Province - Muh. Jazuli Asyrorroji Asyrorroji; Asmannisa Rahmawati; Desi Maola Ayu Saputri (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2025)
High and sustainable economic growth is the main condition or a necessity for the continuity of economic development and the improvement of welfare. Due to the many factors that affect economic growth for a region, it is important to conduct related studies. This study aims to find out the factors that affect economic growth in 38 districts/cities in East Java Province. This study uses secondary data from 2017 to 2023. The model used is a panel data regression model with three types of estimation, namely the Common Effect Model, the Fixed Effect Model and the Random Effect Model. To determine which model is best to use in testing through the Chow Test, Hausman Test and Lagrange Multiplier Test. Based on the results of the tests that have been carried out, the best model is the Random Effect Model. The results of the study show that Labor Force Participation Rate does not have a significant effect on economic growth, while Open Unemployment Rate and Human Development Index have a significant effect on economic growth. Meanwhile, the results of the F test were concluded on the simultaneous influence of the free variable of economic growth on the related variables, namely Open Unemployment Rate, Labor Force Participation Rate and Human Development Index.